A preliminary study of the macroinvertebrate fauna of freshwater habitats in Maludam National Park, Sarawak - E.M. Dosi; J. Grinang; L. Nyanti; K.L. Khoon; M.H. Harun; N. Kamarudin (Mires and Peat, 2018)
Macroinvertebrates are diverse and widespread, and they play important ecological roles in aquatic ecosystems; yet little is known about the macroinvertebrate fauna of the peat swamp forests of Borneo. In light of this knowledge gap, we present a preliminary species list of macroinvertebrates in the peat swamp forest of Maludam National Park, Sarawak, Malaysia. Macroinvertebrates were sampled between April 2011 and November 2014 from three stations on the Maludam River, which flows through the National Park. In total, 3,257 individual macroinvertebrates were examined, representing 37 morpho-species from 20 families and eight orders. Of the total number of individuals captured, 51 % were aquatic beetles (Order Coleoptera), 26 % were aquatic bugs (Hemiptera), 10 % were dragonflies (Odonata), 5 % were flies (Diptera) and 4 % were mayflies (Ephemeroptera). Other orders contributed less than 5 % of the total. The dominant species was the whirligig beetle Dineutus unidentatus (36 % of all individuals caught) which may, thus, be a stenotopic habitat specialist. Despite the harsh environmental conditions of Maludam, where aquatic habitats are acidic and low in dissolved oxygen, the area was found to be inhabited by a diverse macroinvertebrate fauna which is likely to contribute to maintaining the important ecosystem services that the peat swamp forest provides.